Facilitating student-centered teaching and learning - Larioque, Ronaldo R.; Jugo, Luijim S. (Mandaluyong City, 2024)
Optimizing Student-Centered Learning: Comprehending the nuances of student-centered learning and its practical implementation can be demanding. Teachers and students must recognize the distinctions between teacher-centered and student-centered approaches, along with crucial components necessary for cultivating a student-centered learning atmosphere. This book offers a lucid understanding of student-centered learning, accentuating distinct features and methodologies pertinent to curriculum design, embracing student diversity, evaluating influential factors, and employing effective classroom strategies for successful student-centered learning outcomes.
Keywords: Facilitating, Learner-teaching; Teaching